2017
DOI: 10.1016/j.ifacol.2017.08.2241
|View full text |Cite
|
Sign up to set email alerts
|

Principal Process Analysis and reduction of biological models with order of magnitude

Abstract: International audienceWe present a simple method that allows to analyze the biological processes of a dynamical model and classify them. Along the system trajectories, we decompose the model into biological meaningful processes and then study their activity or inactivity during the time evolution of the system. The structure of the model is then reduced to the core mechanisms involving only the active processes. The initial conditions are supposed to lie in some rectangle, that could represent one order of mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In a recent study, we also showed by other methods the robustness of PPA to initial conditions [ 21 ]. The latter were supposed to lie in rectangles contained in a region of the variable space varying by one order of magnitude in each coordinate.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In a recent study, we also showed by other methods the robustness of PPA to initial conditions [ 21 ]. The latter were supposed to lie in rectangles contained in a region of the variable space varying by one order of magnitude in each coordinate.…”
Section: Discussionmentioning
confidence: 90%
“…We hence observed that the negative feedback loop controlling Per and Cry transcription through the formation of the large complex PER-CRY-CLOCK-BMAL1 is the main oscillator, in agreement with previous experimental and modelling studies [ 17 , 25 , 26 ]. Principal Process Analysis has been also applied with success to diverse biogeochemical and biochemical models in our group and elsewhere, see [ 14 , 21 , 28 , 29 ]. These case studies and the present one exemplify the applicability and scalability of the approach to models of diverse nature and and complexity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis allows designing a reduced model, dedicated to the fitting of experimental data, and quantification of physiological parameters. To do so we apply Principal Process Analysis (PPA) [3,4], a numerical method for the analysis and reduction of biological systems designed with ODE formalism. PPA allows associating a dynamic weight to all involved processes and inferring their importance during the acquisition time.…”
mentioning
confidence: 99%